A Cohort Study of Liver Involvement in Patients With Adult-Onset Still's Disease: Prevalence, Characteristics and Impact on Prognosis - Chi, Huihui; Wang, Zhihong; Meng, Jianfen; Han, Pingyang; Zhai, Limin; Feng, Tienan; Teng, Jialin; Sun, Yue; Hu, Qiongyi; Zhang, Hao; Liu, Honglei; Cheng, Xiaobing; et al. (Frontiers in Medicine, 2020)
Objective: Adult-onset Still’s disease (AOSD) is a systemic disorder commonly accompanied by liver involvement. This study aims to illustrate the detailed information of liver abnormalities in patients with AOSD and evaluate the impact on the prognosis. Methods: A total number of 128 hospitalized patients, who met the Yamaguchi criteria of AOSD in the Department of Rheumatology and Immunology, Ruijin Hospital from July 2016 to August 2019 were consecutively enrolled and followed up. The demographic characteristics, clinical features, laboratory tests, treatments and prognosis were recorded. Correlations of liver function tests (LFTs) with disease activity and laboratory parameters were analyzed by the Spearman test. Risk factors of the refractory AOSD were evaluated by multivariate logistic regression analysis. Results: Liver involvement was presented in 104 (81.3%) patients with AOSD. We observed that 34 (32.7%) patients were with mild elevation, 32 (30.8%) patients were with moderate elevation, and 38 (36.5%) patients were with severe elevation. The majority of elevated ALT, AST and ALP decreased to normal within the range of two months, except for GGT. Furthermore, the LFTs were found significantly correlated with disease activity. Besides, we found patients with higher levels of LFTs tended to require more intensive treatments and suffered from poorer prognosis. Multivariate logistic regression analysis showed ALP ≥ 141 IU/L and GGT ≥ 132 IU/L are independent risk factors of refractory AOSD. Conclusion: Liver involvement is common in patients with AOSD, the levels of LFTs are associated with disease activity and related to the treatment strategies and prognosis.